2023
DOI: 10.1101/2023.12.06.570128
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the embodied mind: functional connectome fingerprinting of meditation expertise

Sebastien Czajko,
Jelle Zorn,
Loic Daumail
et al.

Abstract: Short mindfulness-based interventions have gained traction in research due to their positive impact on well-being, cognition, and clinical symptoms across various settings. However, these short-term trainings are viewed as preliminary steps within a more extensive transformative path, presumably leading to long-lasting trait changes. Despite this, little is still known about the brain correlates of meditation traits. To address this gap, we investigated the neural correlates of meditation expertise in long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…This is because both psychedelics (R. Carhart-Harris et al, 2014;R. L. Carhart-Harris, 2018) and meditation (Kakumanu et al, 2018;Vivot et al, 2020;Czajko et al, 2023) have been found to increase brain entropy. Increased entropy (here with regard to psychedelics) is thought to reflect a key phase of the process by which insight occurs.…”
Section: Existing Work On Meditative Deconstruction Under Aif: Advanc...mentioning
confidence: 99%
“…This is because both psychedelics (R. Carhart-Harris et al, 2014;R. L. Carhart-Harris, 2018) and meditation (Kakumanu et al, 2018;Vivot et al, 2020;Czajko et al, 2023) have been found to increase brain entropy. Increased entropy (here with regard to psychedelics) is thought to reflect a key phase of the process by which insight occurs.…”
Section: Existing Work On Meditative Deconstruction Under Aif: Advanc...mentioning
confidence: 99%